2020
DOI: 10.17352/2455-8400.000053
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Rainbow Sardines, Dussumieria acuta (Valenciennes, 1847) from Pakistani waters

Abstract: Small pelagic fi sh are important in the food web of a marine ecosystem, playing a signifi cant role in connecting the lower and upper trophic levels, because a substantial number of predatory fi sh, seabirds and marine mammals feed on them [5, 6, 7]. Fishes belong to family Dussumieriidae is commonly known as round herrings, are small pelagic fi shes widely distributed in tropical and temperate seas, mainly in the Indo-Pacifi c region [8]. Family Dussumieriidae comprises 2 recognized genera and 9 species. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In the past decade, it has been observed that the contribution of sardine landing has increased, which contributed around 4-5% of the total marine harvest in Bangladesh. However, the recent decline in sardine landing was reported in Bangladesh [22], and a similar decline trend was reported in India, Pakistan, and Myanmar waters [21,22,31,32]. However, a wide fluctuation in sardine catch was reported globally and investigated thoroughly [28,29,33].…”
Section: Suitability Of Lbb Methods For Data-poor Sardine Fisherymentioning
confidence: 54%
“…In the past decade, it has been observed that the contribution of sardine landing has increased, which contributed around 4-5% of the total marine harvest in Bangladesh. However, the recent decline in sardine landing was reported in Bangladesh [22], and a similar decline trend was reported in India, Pakistan, and Myanmar waters [21,22,31,32]. However, a wide fluctuation in sardine catch was reported globally and investigated thoroughly [28,29,33].…”
Section: Suitability Of Lbb Methods For Data-poor Sardine Fisherymentioning
confidence: 54%